2009
DOI: 10.1089/jwh.2007.0753
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Examination of Sex Differences in Cardiac Rehabilitation Barriers by Participation Status

Abstract: BACKGROUND-Despite its proven benefits and need, women are significantly less likely to participate in and complete cardiac rehabilitation (CR) than men. The purpose of this study was to quantitatively investigate sex differences in CR barriers by participation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 46 publications
3
117
2
3
Order By: Relevance
“…Cinergis [23][24][25][26] Sabe-se que os programas de RCPM se concentram em promover comportamentos saudáveis e modificações dos fatores de risco, oferecendo além da prescrição de EF a educação em saúde com aconselhamento de um estilo de vida saudável. Neste sentido, este fator tende a ser minimizado com a participação do paciente.…”
Section: Análise Da Aderência Em Diferentes Programas De Reabilitaçãounclassified
“…Cinergis [23][24][25][26] Sabe-se que os programas de RCPM se concentram em promover comportamentos saudáveis e modificações dos fatores de risco, oferecendo além da prescrição de EF a educação em saúde com aconselhamento de um estilo de vida saudável. Neste sentido, este fator tende a ser minimizado com a participação do paciente.…”
Section: Análise Da Aderência Em Diferentes Programas De Reabilitaçãounclassified
“…In fact, it is well established that lack of transportation is a prominent barrier for female cardiac patients (Oldridge, Rogowski & Gottlieb 1992, Lieberman, Meana & Stewart 1998, Halm et al 1999, Allen et al 2004, Grace et al 2009a). For instance, in a multi-site study of 226 female and 507 male CR non-attendees, participants were asked to rate the importance of transportation problems as a barrier to CR utilization (Grace et al 2009a). Ratings were made on a five-point Likert scale, with higher scores indicating greater agreement that transportation serves as a CR barrier.…”
Section: Studies Showing No Relationship Between Cr Utilization and Gmentioning
confidence: 99%
“…Evenson et al (2000) reported that participants who attended more than one session reported distance and transportation were no longer reasons for dropping-out. Finally, in another study 1222 CHD outpatients were asked to rate the importance of almost 20 CR barriers including distance and transportation problems (Grace et al 2009a). As outlined above, ratings were made on a 5-point Likert scale, with higher scores indicating greater agreement that the factor serves as a CR barrier.…”
Section: Studies Reporting Mixed Effects On Cr Utilizationmentioning
confidence: 99%
“…A low level has been shown of CR application in women post-cardiac surgery and hospitalized for extended periods [20]. Grace et al [21] showed that, in comparison with men, women are less willing to participate in CR and more frequently consider physical exercise to be tiring and painful. Women are significantly more likely than men to resign from CR due to greater health problems, particularly concerning skeletal muscles, and for other medical reasons [22].…”
Section: Discussionmentioning
confidence: 99%